2020
DOI: 10.22271/chemi.2020.v8.i4g.9737
|View full text |Cite
|
Sign up to set email alerts
|

Effect of mixing pumpkin powder with wheat flour on physical, nutritional and sensory characteristics of cookies

Abstract: They are usually made cookies with wheat flour which contains a limited amount of β-carotene which is a precursor of vitamin A. Pumpkin is a rich source of β-carotene, which is responsible for its yellow or orange colour. The objective of this study was to determine the optimum level of substitution of carotene rich pumpkin powder (10%) in the formulation and to assess the quality of cookies. The prepared pumpkin powder was assessed for proximate parameters. Cookies were prepared by replacing wheat flour with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…This has been proven in studies [27], where the addition of fruit and vegetable raw materials changed the sensory performance of bread due to coloring substances. Other studies [28] have found that the sweet taste of bread crumb is due to the presence of pumpkin sugar in the paste. Therefore, an increase in the amount of paste helps enhance the expression of sweet taste in bread samples.…”
Section: Discussion Of Results Of the Study Of Expanding The Range Of...mentioning
confidence: 84%
“…This has been proven in studies [27], where the addition of fruit and vegetable raw materials changed the sensory performance of bread due to coloring substances. Other studies [28] have found that the sweet taste of bread crumb is due to the presence of pumpkin sugar in the paste. Therefore, an increase in the amount of paste helps enhance the expression of sweet taste in bread samples.…”
Section: Discussion Of Results Of the Study Of Expanding The Range Of...mentioning
confidence: 84%
“…Fiber is a compound that does not dissolve in water and strengthens the material network; it functions as a texturizer in foodstuffs. So, the higher the fiber content in the raw material, the product with a more rigid, firmer, and more robust texture will be produced (Anitha et al, 2020).…”
Section: Texturementioning
confidence: 99%
“…The poor antioxidant concentration of cookies is one of their usual weaknesses. Innovation is therefore required to raise the antioxidant level of these biscuits (Anitha et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adding pumpkin paste can significantly reduce the calorie content of the finished product and promotes saturation with biologically active substances. However, the specific taste and smell characteristic of pumpkins can reduce sensory quality [27].…”
Section: Determination Of the Optimal Amount Of Pumpkin Paste In The ...mentioning
confidence: 99%